Search for tumor-specific frequencies of amplitude-modulated 27 MHz electromagnetic fields in mice with hepatocarcinoma xenografted tumors. (3rd March 2020) - Veyret, Bernard; Arnaud-Cormos, Delia; Poque, Emmanuelle; Poulletier de Gannes, Florence; Hurtier, Annabelle; Decourt, Rodolphe; Khiev, Sokha; N'Kaoua, Gilles; Lagroye, Isabelle; Lévêque, Philippe; Percherancier, Yann
Abstract: Aim: The Pasche research group has reported that tumor-specific electromagnetic field frequencies have physiological and potential anti-tumor effects in cells, animals, and humans. Our aim was to investigate whether these fields have similar effects on physiological parameters in murine tumor models. Methods: Human HuH7 or HEPG2 cells were implanted in the right flank of 8-week-old female RAG gamma 2 C immunodeficient mice. An oximeter was used to record systolic blood pressure (pulse) in free-roaming conscious mice. Mice pulses were recorded and analyzed using a in-house software that also controlled the low-frequency generator for modulating the 27.12 MHz carrier wave at selected frequencies. Results: We performed exposures using both systematic scans at low frequencies and at the pre-determined frequencies reported by the Pasche group as altering both pulse and tumor growth in humans. Those exposures produced no detectable change in physiological parameters of tumor-bearing mice. Conclusion: No tumor-related frequencies were found, neither using systematic scans of frequencies nor published specific frequencies. There might obviously be differences between animal and human models, but our approach did not confirm the physiological data of the human Pasche group data.